Modification of Kornevin Growth Powder for The Purposes of Root Formation in Semi-Lignified Cuttings of Juníperus Sabína L (London Journal of Research In Science: Natural and Formal, 2025)
In Russian nurseries, growth powders are widely used for rooting semi-lignified cuttings of coniferous crops. Due to the fact that the range of such powders is represented by preparations with only one concentration of the active substance (4 (indol-3-yl) butyric acid) - 5 g / l (0.5% IBA), a study was conducted on the possibility of diluting the preparations with talc and crushed charcoal using the Kornevin powder as an example. Semi-lignified cuttings of Junperus sabna were used in the experiments; rooting was carried out under the conditions of installing low-pressure artificial fog with substrate heating. It was shown that the best option under the experimental conditions was the use of Kornevin-talc powder in a volume ratio of 1 to 1 to stimulate rooting. The rooting of the cuttings was 89.3%. Undiluted Kornevin had a phytotoxic effect, which caused a decrease in the survival rate from the values ??of the best option by 26%. The use of powders with a more significant dilution of Kornevin led to the appearance of signs of auxin deficiency in the stimulator. Thus, it was shown that for rooting cuttings of Junperus sabna, powders with an IMC content of 0.25% are needed, which can be obtained by diluting Kornevin powder with talc or crushed charcoal. It was shown that when diluting growth powder, it is necessary to take into account that with the same degree of dilution (by powder volume), the hormonal properties of IMC decrease more intensively in options with crushed charcoal than talc.
Keywords: pollution; Soil; heavy metals; Siret River sides; propagation; rooting; growth powders; auxins.